The clinical utility of qualitative electroencephalography during tilt table testing – A retrospective study. Issue 4 (April 2018) - Muppidi, Srikanth; Razavi, Babak; Miglis, Mitchell G.; Jaradeh, Safwan
Highlights: Simultaneous EEG recording during tilt table studies does not have significant clinical impact. Not all patients with syncope have EEG changes at the time of the syncope. EEG changes are not seen in other symptomatic orthostatic syndromes. Abstract: Objective: To assess electroencephalography (EEG) changes during tilt table testing in syncope and other orthostatic syndromes. Methods: We retrospectively reviewed consecutive tilt table studies with simultaneous EEG from April 2014 to May 2016 at our center. All patients had video EEG during tilt table. All patients had at least 10 min of head up tilt unless they had syncope or did not tolerate the study. Video EEG was interpreted by epileptologists. Results: Eighty-seven patients met the inclusion criteria. Mean age was 45 years, and 55 were women. Seven patients (∼8%) had syncope during tilt table, 11 patients (∼12%) had significant neurogenic orthostatic hypotension and a separate group of 11 patients (∼12%) had significant orthostatic tachycardia. Valsalva responses were abnormal in 7 of the 11 patients with orthostatic hypotension, suggesting an underlying neurogenic orthostatic hypotension. Visually discernable EEG changes were seen in only 3 patients (∼43%) who had syncope and in 1 patient (∼9%) with orthostatic tachycardia. Conclusions: Qualitative EEG analysis based on visual inspection during tilt table study revealed abnormalities in less than half the patients with syncope and a very small fraction with orthostatic tachycardia. Significance: Routine qualitative EEG recording might not be clinically useful during tilt table studies.